Examining mental workload based on multiple physiological signals: Review of the multi-attribute task battery (MATB) technique - Jiapu Chai; Yan Li (Medicine in Novel Technology and Devices)
MATB (Multi-Attribute Task Battery), developed by NASA, simulates real-world task demands and work environments. It assesses human cognitive and executive abilities in high-load, complex task settings, as well as their adaptive capacity for task switching and attention allocation. This article reviews MATB's primary applications and usage, exploring mental workload-related research with MATB, analyzing experimental procedure design, objective physiological signals, and model construction. This analysis facilitates a comprehensive understanding of utilizing MATB for mental workload experiments and improving experimental design. Additionally, it proposes a more comprehensive and scientific experimental procedure for cognitive load research using MATB. Through this review, researchers gain insights into the versatility and potential of MATB as a tool for assessing mental workload and optimizing experimental design in various fields.